2021
DOI: 10.3389/fped.2021.640995
|View full text |Cite
|
Sign up to set email alerts
|

Endourology Methods in Pediatric Population for Kidney Stones Located in Lower Calyx: FlexURS vs. Micro PCNL (MicroPERC®)

Abstract: Kidney stone disease in children is always a therapeutic challenge. It is a multifactorial condition and it should be approached, diagnosed and treated as such. One of the biggest challenges is kidney stones located in the lower renal calyx. There are currently three main surgical techniques to treat this condition: ESWL—Extracorporeal Shock Wave Lithotripsy, RIRS—Retrograde IntraRenal Surgery, and PCNL—PerCutaneous Nephro-Lithotripsy. In pediatric population, the most frequently used method is ESWL, and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…In a retrospective study including 24 infants undergoing “micro-PNL” for renal stones, Dede et al ( 18 ) recorded a stone-free rate of 83.3% with 4 patients complaining of post-operative renal colic and 2 patients experiencing post-operative fever. Similarly, a stone-free rate of 86.7% was reported in a recent paper involving 15 patients undergoing “micro-PCNL” for kidney stones located in lower calyx ( 19 ).…”
Section: Miniaturized Technologiessupporting
confidence: 52%
“…In a retrospective study including 24 infants undergoing “micro-PNL” for renal stones, Dede et al ( 18 ) recorded a stone-free rate of 83.3% with 4 patients complaining of post-operative renal colic and 2 patients experiencing post-operative fever. Similarly, a stone-free rate of 86.7% was reported in a recent paper involving 15 patients undergoing “micro-PCNL” for kidney stones located in lower calyx ( 19 ).…”
Section: Miniaturized Technologiessupporting
confidence: 52%
“…Following the full-text article evaluation, 11 articles were excluded. The remaining four articles [ [12] , [13] , [14] , [15] ] were further analyzed as presented in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to be feasible and may be more effective in pediatric patients [ 11 ]. Recent studies comparing Micro-PCNL and RIRS in pediatrics indicated that these procedures have their respective advantages and disadvantages [ [12] , [13] , [14] , [15] ]. In this review, we aim to evaluate the efficacy and safety between Micro-PCNL and RIRS in treating moderately sized pediatric kidney stones.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a proportion of the patients need additional auxiliary procedures to achieve complete stone clearance. The main contraindications for ESWL in children are coagulation dysfunction, cardiopulmonary disease, lithotripsy passage obstruction, uncontrolled urinary tract infection, diabetes, skeletal malformations, excessive obesity, active infectious diseases, renal insufficiency, and hemangioma around the stone ( 6 , 17 ).…”
Section: Literature Searchmentioning
confidence: 99%
“…In the past decades, the treatment methods for PU have changed dramatically because of the development of equipment, technological innovation, and the increasing experience of pediatric urologists. The original traditional open surgery is replaced by the current minimally invasive surgeries, including extracorporeal shockwave lithotripsy (ESWL), ureteroscopy (URS), and retrograde intrarenal surgery (RIRS), percutaneous nephrolithotomy (PCNL), laparoscopic, and robot-assisted surgery ( 5 , 6 ). Since there are many minimally invasive treatment methods, pediatric urologists must be familiar with the advantages and shortcomings of each treatment option.…”
Section: Introductionmentioning
confidence: 99%